Resurrecting the role of real money balance effects - José Dorich (Bank of Canada, 2009)
I present a structural econometric analysis supporting the hypothesis that money is still relevant for shaping inflation and output dynamics in the United States. In particular, I find that real money balance effects are quantitatively important, although smaller than they used to be in the early postwar period. Moreover, I show three additional implications of the econometric estimates for monetary policy analysis. First, by including real money balance effects into the standard sticky price model, two stylized facts can be explained: the modestly procyclical real wage response to a monetary policy shock and the supply side effects of monetary policy. Second, the existence of real money balance effects causes higher volatility of output and lower volatility of interest rates under the optimal monetary policy. Third, the reduction in the size of real money balance effects can account for a significant decline in macroeconomic volatility.
Keywords: E31; E32; E52; 330; Business fluctutations and cycles; Monetary aggregates; Transmission of monetary policy; Geldpolitik; Transmissionsmechanismus; Inflation; Gesamtwirtschaftliche Produktion; Lohnniveau; USA